Review of the sylvatic cycle of African swine fever in sub-Saharan Africa and the Indian ocean - (:unkn) unknown (My University, 2013)
African swine fever (ASF) is a major limiting factor for pig production in most of the countries in Sub-Saharan Africa and the Indian Ocean. In the absence of vaccine, a good understanding of the ecology and epidemiology of the disease is fundamental to implement effective control measures. In selected countries of Southern and East Africa, the association between Ornithodoros moubata ticks and warthogs has been described in detail in the literature. However, for many other countries in the region, information related to the sylvatic cycle is lacking or incomplete. In West African countries, for instance, the role of wild pigs in the epidemiology of ASF has never been demonstrated and the existence and potential impact of a sylvatic cycle involving an association between soft ticks and warthogs is questionable. In other countries, other wild pig species such as the bushpigs (Potamochoerus spp.) can also be asymptomatically infected by the virus but their role in the epidemiology of the disease is unclear and might differ according to geographic regions. In addition, the methods and techniques required to study the role of wild hosts in ASF virus (ASFV) epidemiology and ecology are very specific and differ from the more traditional methods to study domestic pigs or other tick species. The aim of this review is (i) to provide a descriptive list of the methodologies implemented to study the role of wild hosts in African swine fever, (ii) to compile the available knowledge about the sylvatic cycle of ASFV in different regions of Sub-Saharan Africa and the Indian Ocean in addition to the one that has been described for East and Southern Africa, and (iii) to discuss current methodologies and available knowledge in order to identify new orientations for further field and experimental surveys.
Keywords: African Research